Cone Beam Computed Tomography(CBCT) Features Of A Rare Fibro-Osseous Lesion: A Case Report - Mahrokh Imanimoghaddam; Hassan Hosien pour Jajarm; Nasrolah Saghravanian; Maryam Mohammadzadeh Rezaei; Samareh Mortazavi (Mashhad University of Medical Sciences, 2013)
Cone beam computed tomography is a useful technique for imaging the craniofacial lesions. It produces more realistic images that facilitate interpretation. Juvenile ossifying fibroma (JOF) is a rare and benign fibro-osseous neoplasm that arises within the craniofacial bones, especially in the maxilla. Mandibular lesions can be seen in 10% of the cases.In both jaws, it has a predilection for the premolar and molar regions (it is mostly seen in premolar and molar regions). Radiographically, it can be present as a radiolucent, mixed or radiopaque lesion. Radiodensity varies from purely radiolucent masses to mixed densities with prominent radiopacity as the lesion matures. This case report highlights a JOF with large foci of odontome-like radiopacities in a 6-year-old boy's mandibular anterior region. The location of the lesion in the anterior mandible and comparatively rapid formation of large odontome-like radiopaque foci at this early agehas made it a rare entity.